1996
DOI: 10.1095/biolreprod55.6.1284
|View full text |Cite
|
Sign up to set email alerts
|

RU486-Treated Rats Show Endocrine and Morphological Responses to Therapies Analogous to Responses of Women with Polycystic Ovary Syndrome Treated with Similar Therapies1

Abstract: Administration of 4 mg of the antiprogestagen RU486 to 4-day-cyclic rats over 8 consecutive days starting on the day of estrus (Day 1) induced and anovulatory cystic ovarian condition with endocrine and morphological features similar to those exhibited in polycystic ovarian disease (PCO). To determine whether the RU486-treated rat responds in an analogous fashion to therapies similar to those that have been used to treat human PCO, RU486-treated rats were injection on Days 5 and 7 with 1) 1 mg of an LHRH antag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 29 publications
6
24
0
Order By: Relevance
“…Following 2-4 days of injection of mifepristone, the normal estrous cycles were disturbed to be 'persistent vaginal cornification' or consecutive estrous stage until the time of tissue fixation (Ruiz et al 1996). The persistent vaginal smear was consistent with the findings of previous report using the oral administration of mifepristone (Gao & Short 1994).…”
Section: Histological Examination Of Mouse Ovaries After Injection Ofsupporting
confidence: 87%
See 2 more Smart Citations
“…Following 2-4 days of injection of mifepristone, the normal estrous cycles were disturbed to be 'persistent vaginal cornification' or consecutive estrous stage until the time of tissue fixation (Ruiz et al 1996). The persistent vaginal smear was consistent with the findings of previous report using the oral administration of mifepristone (Gao & Short 1994).…”
Section: Histological Examination Of Mouse Ovaries After Injection Ofsupporting
confidence: 87%
“…However, the administration of mifepristone to rats was recently used as a good model of human PCO syndrome (Singh 2005, Lakhani et al 2006. The mifepristone-induced PCO syndrome model in rats is appropriate in some aspects to simulate the PCO syndrome condition of ovaries in humans, because not only ovarian histology but also the hormone levels were quite similar to those of humans (Sanchez-Criado et al 1992, 1993, Ruiz et al 1996. Although these studies showed that the mifepristone-induced PCO syndrome model was reversible during the experimental course (Singh 2005), the PCO syndrome model is useful for histopathological studies on the mechanism of chronic anovulation and vascular functions in greater detail, considering the recent technical development of transgenic animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These discrepancies may be due to the different origins of FF (human vs. bovine), to the experimental model used (static vs. dynamic incubation) and to the absence or presence of inhibin. Previous results published by this research group (Tébar et al, 1996(Tébar et al, , 1998 support the hypothesis that the pituitary loses sensitivity to attenuin when follicles reach the preovulatory size, which would account for estradiol suddenly exerting a positive feedback. This intriguing mechanism, by which pituitaries become insensitive to attenuin and/or sensitive to the stimulatory action of GnRH, may provide an extra clue for understanding estrous cycle length regulation.…”
Section: Ratssupporting
confidence: 60%
“…This factor would limit the physiological timing (proestrous afternoon) as well as the magnitude (preovulatory secretion) of pituitary responsiveness to GnRH. This research thus shows how a decrease in endogenous FSH levels during diestrus, with a consequent reduction in attenuin production but no significant effect on estradiol levels, gives rise to a 1-or 2-day advancement of blunted preovulatory LH surges in 4- (Tébar et al, 1996, 1998) and 5-day (Sánchez-Criado et al, 1996 cyclic rats, respectively. This suggests that, in physiological circumstances, submaximal FSHdependent ovarian attenuin bioactivity prevents the premature LH surge in diestrus by antagonizing the secretory effect of GnRH (Koppenaal et al, 1991;Tébar et al, 1998) and/or the sensitizing effect of estradiol on the pituitary (Schuiling et al, 1999).…”
Section: Ratsmentioning
confidence: 68%